(untitled) (Annals of Medical Research, 2021)
Aim: Autoimmune hemolytic anemia (AIHA) is a rare disease in pediatrics, whose mortality rate was reported to be as high as 10%. AIHA can be primary or secondary to other diseases, Availability of new immunsupressive drugs like mycofenolate mofetil (MMF), has provided the opportunity to reduce long term steroid administration and mortality. In this study we aimed to represent AIHA patients of 20 years, from single centre and focus on the causes, treatment and outcomes. The secondary object was to represent outcomes of patients who received MMF.Material and Methods: This study was designed as a retrospective study. Patients aged three months to 18 years old with hemoglobin level less than 10 g/dl and positive DAT with signs of hemolysis were included in the study.Results: Twenty five AIHA patients (F/ M: 14/ 11) aged 6.2± 4.6 years old were followed- up for a mean period of 5.3± 4.8 years. Primary AIHA was detected in 12 (48%) patients. Immune deficiency/ autoimmune lymphoproliferative syndrome was the prominent etiological factor in secondary AIHA. The other underlying diseases were systemic lupus erythematosus, malignancy, autoimmune hepatitis and infection.Eleven patients received MMF with a mean duration of 2.6± 1.6 years. Two of them had primary AIHA, the others had secondary disease. During the follow- up time, eight patients (75%) achieved remission with MMF. None of MMF users developed side effect. One but all patients with AIHA achieved remission. No death related to AIHA was recorde’: recorded Conclusion: Understanding the biology of the disease and making accurate diagnosis is important to avoid harmful treatment and to consider targeted therapy. After the failure of first line therapy with steroids or as a steroid- sparing agent, MMF seems to be an effective second-line maintanance immunosuppressive drug without significant side effects.